2.4y+13+(-6.5y)=0.24y-8.85+(-6y)

Simple and best practice solution for 2.4y+13+(-6.5y)=0.24y-8.85+(-6y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.4y+13+(-6.5y)=0.24y-8.85+(-6y) equation:



2.4y+13+(-6.5y)=0.24y-8.85+(-6y)
We move all terms to the left:
2.4y+13+(-6.5y)-(0.24y-8.85+(-6y))=0
We get rid of parentheses
2.4y-6.5y-(0.24y-8.85+(-6y))+13=0
We calculate terms in parentheses: -(0.24y-8.85+(-6y)), so:
0.24y-8.85+(-6y)
determiningTheFunctionDomain 0.24y+(-6y)-8.85
We get rid of parentheses
0.24y-6y-8.85
We add all the numbers together, and all the variables
-5.76y-8.85
Back to the equation:
-(-5.76y-8.85)
We add all the numbers together, and all the variables
-4.1y-(-5.76y-8.85)+13=0
We get rid of parentheses
-4.1y+5.76y+8.85+13=0
We add all the numbers together, and all the variables
1.66y+21.85=0
We move all terms containing y to the left, all other terms to the right
1.66y=-21.85
y=-21.85/1.66
y=-13+0.27/1.66

See similar equations:

| (5x)x2=(2x)x14 | | 7−9j=–8j | | -10-5y=-7y+10 | | –7+–3t=–19 | | ×-3=2x-3-x | | 9=4a+4 | | –3=6v | | 33/4=r×1/8 | | 8d−8=–8+8d | | -4w+8=-5w+11 | | (3r-35)+(-2r+90)=180 | | x/7=154 | | √4x3+54=3 | | (12x-32)+(3x+32)=180 | | -2-8k=-8k-2 | | 324+12=442x | | 23-5(2x-9)=-5x+11+4 | | -45+2b-b=15 | | 41=4x–3 | | 1/4x+-1+1/23=-20 | | 12.51-4=p | | g-2/3=9/g | | 28x+48+16x=180 | | F=2h+8 | | -5c+3=-4c-7 | | –9s=8−5s | | 6+0.90x=1.50 | | -3.8z=30.4 | | 16w=12w+36 | | –8h+4=–5h−2 | | 23x+12=-12 | | -2y-13=-43 |

Equations solver categories